Nonmuscle-invasive bladder cancer, old problems, new insights. Issue 4 (July 2022) - Compérat, Eva; Wasinger, Gabriel; Oszwald, André; Pradere, Benjamin; Shariat, Shahrokh
Abstract : Purpose of review: Nonmuscle-invasive bladder cancer (NMIBC) is the most frequent bladder cancer and represents around 75% of bladder cancers. This review will discuss known challenges and recent advances in staging, grading and treatment stratification based on pathology. Recent findings: Pathological staging and grading in NMIBC remains challenging and different techniques exist. Substaging has been shown to be of prognostic relevance and to help predict treatment response in patients receiving Bacillus Calmette-Guérin (BCG) therapy, which is the treatment of choice for high-grade NMIBC. Recent advances in molecular classification and artificial intelligence were also able to show promising results in the stratification of patients. Summary: Many challenges in the diagnosis of NMIBC are still unresolved and ask for more prospective research. New technologies, molecular insights and AI will help in the upcoming years to better stratify and manage these patients.